Innovation of Tourism Icons through Blender Software Utilizing Natural Fibers in Sukoharjo - Pertiwi, Ayu Ratna; Sumarno; Indarto (Institut Seni Indonesia Surakarta, 2023)
Tourism, as an economic sector with significant potential, requires attractions that can be drawn from various aspects, including icons. These icons, rooted in local characteristics and culture, can be transformed into statues, monuments, and other forms of representation. However, sculpture creation poses a challenge for communities lacking adequate knowledge and skills. Natural fibers, such as bamboo, hemp, tree bark, rattan, and straw, are abundant materials that can be utilized for this purpose. Trangsan Village in Sukoharjo Regency, Central Java, is one area with tourism potential that currently lacks icons and branding. This research aims to develop methods for creating sculpture or tourism icons by translating 3D software models into life-sized objects or prototypes. The research stages include observation and data analysis, determination of tourism icons, 3D modeling, and post-modeling by composing fragment images as anatomical references. The subsequent processes involve creating and materializing prototypes, protecting intellectual property rights, and conducting public tests. This study addresses the challenge of icon creation in underdeveloped tourism areas and offers a systematic approach for integrating traditional craftsmanship with modern technology to enhance local tourism branding.